Evolution of the Role of the Agricultural Sector in the Food Security of Jordan: - A SWOT Analysis after a Century of Establishment - Jabarin, Amer Subhi (Jordan Journal of Agricultural Sciences, 2021)
In 1921, the population of the Emirate of Transjordan was only 230 thousand people. The newly born country had few natural resources and few population centers, and its only real revenue was British government aid. The latest statistics show that Jordan’s population amounted to 10.96 million in August 2020, which means that the population has increased by more than 46 folds over the last 100 years. The huge increase in the kingdom’s population has put huge pressures on the limited resources available to the agricultural sector and consequently jeopardize the food security situation, especially in the last few decades. Food security in Jordan is a complex issue which exacerbated during the latest Covid-19 epidemic which coincided with the ongoing refugee crises. The main objective of this paper is to explore the main directions of the expected role of the agricultural sector and its impact on the food security situation in Jordan in the next century. The researcher used a descriptive analysis tool that uses the points of strengths (S), weakness (W), opportunities (O), and threats (T) (SWOT) to achieve the objective of this research. The main conclusions drawn from the SWOT analysis conducted in this paper are as follows: 1)climate change and the decline in the very scarce water resource is the major challenge that is currently facing and will continue to face the agricultural sector which will jeopardize the food security system in Jordan, 2) another major challenge is the high population growth rates and a large number of refugees in the country, 3) The absence of clear and robust food security policy, and 4) Food waste and post-harvest losses are another major threat of the food security in Jordan. To minimize these challenges, the researcher recommends the following that: 1) Increase the water use efficiency of the current agricultural production systems through adopting new irrigation techniques such as improved drip irrigation systems, 2) expand in the hydroponic production systems that save huge amounts of irrigation water which could also be produced near urban centers to save transportation costs of final production, 3) introduce drought-resistant varieties of field crops, forage crops and trees, 4) improve the post-harvest handling systems of perishable agricultural products to reduce losses across the different stages of the value chain such expanding with cold storage facilities, cold trucks, pre-cooling, and proper packing and packaging, 5) improve the agricultural education curricula through establishing new programs that meet the current and future food market demand, and 6) support and encourage young researchers through incubating and accelerating their new ideas which could add great values to the current agricultural and food security system in Jordan.